Dedicated plug based closure for large bore access -The MARVEL prospective registry - Kroon HG (Wiley, 2022)
Objectives To study safety and performance of the MANTA Vascular closure device (VCD) under real world conditions in 10 centers.Background The MANTA is a novel plug-based device for large bore arteriotomy closure.Methods We included all eligible patients who underwent transfemoral large bore percutaneous procedures. Exclusion criteria were per operator's discretion and included severe calcification or marked tortuosity of the access vessel, presence of marked obesity/cachexia or a systolic blood pressure above 180 mmHg. The primary performance endpoint was time to hemostasis. Primary and secondary safety endpoints were major and minor access site related vascular complications up to 30 days, respectively. Vascular complications were adjudicated by an independent clinical event committee according to VARC-2 criteria. We performed multivariable logistic regression to estimate the effect of baseline and procedural characteristics on any and major vascular complications.Results Between February 2018 and July 2019 500 patients were enrolled undergoing Transcatheter aortic valve replacement (TAVR, N = 496), Balloon aortic valvuloplasty (BAV, N = 2), Mechanical circulatory support (MCS, N = 1) or Endovascular aneurysm repair (EVAR, N = 1). Mean age was 80.8 +/- 6.6 years with a median STS-score of 2.7 [IQR 2.0-4.3] %. MANTA access site complications were major in 20 (4%) and minor in 28 patients (5.6%). Median time to hemostasis was 50 [IQR 20-120] sec. Severe femoral artery calcification, scar presence in groin, longer procedure duration, female gender and history of hypertension were independent predictors for vascular complications.Conclusion In this study, MANTA appeared to be a safe and effective device for large bore access closure under real-world conditions.